The doctor's guide to gastrointestinal health : preventing and treating acid reflux, ulcers, irritable bowel syndrome, diverticulitis, celiac disease, colon cancer, pancreatitis, cirrhosis, hernias, and more - Miskovitz, Paul F. (John Wiley, 2005)
A comprehensive guide to gastrointestinal health that provides information on preventing, diagnosing, and treating various disorders, including acid reflux, ulcers, diverticulitis, colon cancer, pancreatitis, and more.